2010
DOI: 10.1007/s10661-009-1254-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of diatom biotic indices in the Guadalquivir River Basin, a Mediterranean basin. Which one is the most appropriated?

Abstract: The diatom community was studied in 110 sites within the Guadalquivir River catchment area, South Spain, in order to test the applicability of diatom biotic indices developed in other European regions to this site and to provide a useful tool for monitoring water quality in the river basin. We identified 399 taxa and calculated five diatomic indices (Specific Polluosensitivity Index (IPS), Biological Diatom Index, Trophic Diatom Index, Index of the European Economic Community, and Diatom-based Eutrophication P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 34 publications
(21 reference statements)
1
17
0
Order By: Relevance
“…The summary of environmental data is shown in Table 1. Previous studies on Achnanthidium stated that species of this genus live in alkaline to acidic environments [14]; this is supported by the results of the present study. Achnanthidium ovale and A. minutissimum were collected from an alkaline environment, whereas A. cavitatum was collected from an acidic environment.…”
Section: Ecological Characteristics Of Two Achnanthidium Speciessupporting
confidence: 92%
“…The summary of environmental data is shown in Table 1. Previous studies on Achnanthidium stated that species of this genus live in alkaline to acidic environments [14]; this is supported by the results of the present study. Achnanthidium ovale and A. minutissimum were collected from an alkaline environment, whereas A. cavitatum was collected from an acidic environment.…”
Section: Ecological Characteristics Of Two Achnanthidium Speciessupporting
confidence: 92%
“…Nitzschia frustulum commonly found in various habitats such as fresh, coastal and marine waters. Some Nitzschia species are indicators of heavy metal contamination and eutrophic conditions [19]. Pinnularia divergentissima was abundant species and commonly found in TP 4.…”
Section: Resultsmentioning
confidence: 99%
“…However, EPI-D has given extremely good results in Italian Mediterranean Rivers (Dell'Uomo et al, 1999 andTorrisi andDell'Uomo, 2006). Martin et al (2010) found that the application of the EPI-D diatom index is recommended because of its inherent advantages. An important reason for the failure of the application of these diatomic indices is the great differences between the species pool present in the area of study with regions where these indices developed.…”
Section: Discussionmentioning
confidence: 99%